METHODOLOGY OF DEVELOPING PROFESSIONAL CULTURE OF COLLEGE STUDENTS ON THE BASIS OF COMPETENCY APPROACH - Xolmatova, Salima (Журнал иностранных языков и лингвистики, 2021)
Improving the professional culture of college students in developed countries on the basis of a competency approach, increasing mobilization and promoting innovative approaches and technology-based professional activities in education, inculcating personal and professional qualities, philosophical and professional views, components of professional culture (motivational-value, special attention is paid to research on improving the methods, technologies, forms and means of cognitive, functional) development. The development of theoretical and practical bases of these directions, the definition of its psychological and pedagogical factors and conditions, content and structure, plays an important role in training highly qualified professionals in the period of social renewal and spiritual growth.